(untitled) (Medico Legal Update, 2021)
Objective: This study examined patients’ complain regarding pain on eating, esthetic and speech problems and gag reflex with various types of removable partial dentures (RPDs). Method: The study sample included 60 RPD wearers (36 females and 24 males) aged between (25-60) years old. Sex, age, occupation, any experience with previous RPDs, and the complaint with RPDs were recorded. Data were analyzed using Chi-square test was applied for comparison among different variables of oral complaints related to removable prosthesis; an independent a sample t-test was utilized. A P-value < 0.01 was the criterion for rejection of the invalid hypothesis. Results: the results show 60 patients, 16 (47.05%) were satisfied on acrylic and14 (77.77%) were satisfied on flexible. And 6 (75%) were satisfied on metallic. The mean level of satisfaction among the three types of RPDs was significantly different (P < 0.01). In cases satisfaction between flexible and acrylic RPDs was significantly different. But, between either metal or acrylic, or metal and flexible RPDs no significant differences (P < 0.01) were recognized. Conclusions: Within the limitations of this study, approximately half of cases that tooka removable partial dentures treatment were satisfied with it, showing that the quality of RPDs(in Iraq/Baghdad city) was suitable for patients. Pain in eatingis the most common complaint that shows that dental treatments with RPDs should be provided with care when patients have pain in eating.